Rapid Electrochemical Assessment of Tumor Suppressor Gene Methylations in Raw Human Serum and Tumor Cells and Tissues Using Immunomagnetic Beads and Selective DNA Hybridization. Issue 27 (6th June 2018) - Povedano, Eloy; Valverde, Alejandro; Montiel, Víctor Ruiz‐Valdepeñas; Pedrero, María; Yáñez‐Sedeño, Paloma; Barderas, Rodrigo; San Segundo‐Acosta, Pablo; Peláez‐García, Alberto; Mendiola, Marta; Hardisson, David; Campuzano, Susana; Pingarrón, José M.
Abstract: We report a rapid and sensitive electrochemical strategy for the detection of gene‐specific 5‐methylcytosine DNA methylation. Magnetic beads (MBs) modified with an antibody for 5‐methylcytosines (5‐mC) are used for the capture of any 5‐mC methylated single‐stranded (ss)DNA sequence. A flanking region next to the 5‐mCs of the captured methylated ssDNA is recognized by hybridization with a synthetic biotinylated DNA sequence. Amperometric transduction at disposable screen‐printed carbon electrodes (SPCEs) is employed. The developed biosensor has a dynamic range from 3.9 to 500 pm and a limit of detection of 1.2 pm for the methylated synthetic sequence of the tumor suppressor gene O ‐6‐methylguanine‐DNA methyltransferase ( MGMT ) promoter region. The method is applied in the 45‐min analysis of specific methylation in the MGMT promoter region directly in raw spiked human serum samples and in genomic DNA extracted from U‐87 glioblastoma cells and paraffin‐embedded brain tumor tissues without any amplification and pretreatment step. Abstract : An immuno‐DNA electrochemical sensor for the rapid assessment of tumor suppressor gene methylations in raw human serum, tumor cells, and cancer tissues is presented.